Clinical value of circulating tumor cells for the diagnosis and prognosis of hepatocellular carcinoma (HCC): A systematic review and meta-analysis - Cui, Kai (Medicine (Baltimore), 2020)
BACKGROUND: To evaluate the clinical value of circulating tumor cell (CTC) detection in peripheral blood for the diagnosis and prognosis of hepatocellular carcinoma (HCC). METHODS: Public databases were searched, and a meta-analysis was performed to determine the specificity, sensitivity, negative- likelihood ratio (NLR) and positive-likelihood ratio (PLR), and diagnostic odds ratio (dOR) of CTC detection for the diagnosis of HCC. Hazard ratios (HRs) and 95% confidence intervals (CIs) were analyzed for the association of CTC detection with overall survival (OS) and HCC recurrence. The Meta-DiSc 1.4 and Review Manager 5.2 software programs were used for statistical analysis. RESULTS: Meta-analysis of 20 studies including 1191 patients showed that the specificity, sensitivity, NLR, PLR, and dOR of CTC testing for HCC diagnosis were 0.60 (95% CI = 0.57–0.63), 0.95 (95%CI = 0.93–0.96), 0.36 (95%CI = 0.28–0.48), 11.64 (95%CI = 5.85–23.14), and 38.94 (95%CI = 18.33–82.75), respectively. Meta-analysis of 18 studies including 1466 patients indicated that the OS of CTC-positive HCC patients was less than that of CTC-negative patients (HR = 2.31; 95% CI = 1.55–3.42; P < .01). Meta-analysis of 5 studies including 339 patients revealed that the presence of CTCs in peripheral blood significantly increased the risk of HCC recurrence (HR = 3.03, 95% CI = 1.89–4.86; P < .01). CONCLUSION: CTCs in peripheral blood may be a useful marker for HCC diagnosis. In addition, the prognosis of CTC-positive HCC patients was significantly worse than that of CTC-negative HCC patients. Therefore, further studies are warranted to confirm the clinical potential of CTC detection in peripheral blood in patients with primary HCC.